FOUNDATIONS OF PROFESSIONAL COMPETENCE FOR THE OFFICERS OF THE SPECIAL SETTING OF NATIONAL GUARD OF UKRAINE: THEORETICAL ASPECT - Bolotnuy, I. (Continuing Professional Education: Theory and Practice, 2019)
In the article the basic stages of history of kompetentnostnogo approach are described in education, general theoretic bases of forming of professional jurisdiction are analysed. And also pedagogical terms of its efficiency for the officers of the special setting of The National Guard of Ukraine. In the establishment and development of conceptual provisions reforming the law enforcement system of Ukraine was the transfer of authority to the Internal Troops of the restored National Guard of Ukraine on 13 March 2014. The main tasks of the National Guard of Ukraine classified national security and protection of state borders, combating terrorism, and Illegal paramilitary or armed groups (groups) and others. Analyzed the concept of competence, competence and professional competence suggest an integrated approach to the profession of law enforcement officers and, in particular, to its formation in special purpose officers of the National Guard of Ukraine. In establishing competency approach taken to provide three periods: the first and second 50th and 70th years of the twentieth century, three 90s -early late twentieth century XXI. By components of professional competence special units of the National Guard Ukraine we include professional knowledge and skills; professional values and personality; a high level of self-organization and rapid response to extreme circumstances. There are many classifications of competencies that are generally divided into top and cover that also to restore professional competence and have a universal character. In the formation of professional competence of officers in the training of Special Forces we have identified the following types of competencies as social, legal, psychological, of the conflict, communication, ability to learn, personal and extreme. In pedagogical terms, we understand the deliberate creation of conditions of integrative factors … for the effective achievement of the educational process. training, feedback in the tasks and analyze their results. system control measures.